Dynamic kinematics of the glenohumeral joint in shoulders with rotator cuff tears - Kozono, Naoya (J Orthop Surg Res, 2018)
BACKGROUND: No clear trend has emerged from the literature regarding three-dimensional (3D) translations of the humerus relative to the scapula in shoulders with rotator cuff tears (RCTs). The purpose of this study was to evaluate the kinematics of RCT shoulders using 3D-to-two-dimensional (2D) model-to-image registration techniques. METHODS: Dynamic glenohumeral kinematics during scapular plane abduction and axial rotation were analyzed in 11 RCT patients and 10 healthy control subjects. We measured the 3D kinematic parameters of glenohumeral joints using X-ray images and CT-derived digitally reconstructed radiographs. RESULTS: For scapular plane abduction, the humeral head center was positioned significantly more medially in shoulders with RCTs than in controls at 135° of humeral abduction (p = 0.02; RCTs versus controls: − 0.9 ± 1.6 versus 0.3 ± 1.3 mm). There was no significant difference in the superior/inferior translation of the humeral head center (p = 0.99). For axial rotation in adducted position, the humeral head center was positioned significantly more anteriorly in shoulders with RCTs than in controls at − 30° of glenohumeral external rotation (p < 0.0001; RCTs versus controls: 3.0 ± 1.7 versus 0.3 ± 1.5 mm). CONCLUSIONS: This study revealed the kinematics of shoulders with large to massive full-thickness RCTs: the humeral head center showed a medial shift at the late phase of scapular plane full abduction, and an anterior shift at the internal rotation position during full axial rotation. The kinematic data in this study, which describe the patterns of movement of shoulders with large to massive full-thickness RCTs, provide valuable information for future studies investigating glenohumeral translations in other pathological conditions of the shoulder. For clinical relevance, quantitative assessment of the dynamic kinematics of shoulders with RCTs might be a therapeutic indicator for achieving functional restoration.